Global Biodiversity : Volume 3: Selected Countries in Africa - Pullaiah, T.; Apple Academic Press (Toronto ; New Jersey : Apple Academic Press, 2018)
This is the third volume in the new multi-volume set, Global Biodiversity. Each volume in this series covers the biodiversity of a selection of nations in particular regions of the world. The volumes discuss and summarize the available information on both wild and cultivated plants, wild and domesticated animals, and the variety of microbes of the different nations. This volume looks at the biodiversity of selected countries of Africa, providing a rich resource of biodiversity information on countries in different parts of Africa, including: Libya, Morocco, and Egypt in North Africa countries on the east coast, including Gabon, Ghana, Sierra Leone, Togo, Senegal land-locked countries, including Burkina Faso and Zambia, countries on the west coast, including Sudan, Tanzania and South Africa With chapters written by research scientists and conservationists, the book covers geographical status, ecosystem diversity, species diversity, genetic diversity, and conservation efforts in each selected country. The authors provide statistical data on plants, animals, and microbes of that country along with genetic diversity with the focus on crop plants/cultivated plants and domesticated animals and their wild relatives. Endangered plants and animals and protected areas are discussed. Other volumes in this series include coverage of selected countries in Asia, Europe, the Americas, and Australia.
Phytodiversity of Burkina Faso -- Nacoulma Blandine Marie Ivette et al. -- Biodiversity in Egypt -- Wafaa M. Amer -- Biodiversity of Gabon: An Overview -- Jean B. Mikissa, Flore Koumba Pambou, and Emmanuel Bayani Ngoyi -- Biodiversity in Ghana -- Michael Kwabena Osei et al. -- Biodiversity of Libya -- Mahklouf H. Mohammed and Etayeb S. Khalid -- Biological Diversity in Morocco -- Mohamaed Menioui -- Biodiversity of Senegal: Terrestrial Ecosystems Flora and Great Fauna -- Gueye Mathieu, Ba Tabou, and Diop Sall Aminata -- Biodiversity in Sierra Leone -- Prince E. Norman et al. -- Biodiversity of South Africa -- Danni Guo and Judith L. Arnolds -- Biodiversity of Sudan -- Ahmed A. H. Siddig et al. -- An Overview of Biodiversity of Tanzania and Conservation Efforts -- Ally K. Nkwabi et al. -- Biodiversity in Togo -- Kouami Kokou et al. -- Biodiversity of Zambia -- Stanford Mudenda Siachoono.
Includes bibliographical references and index.
Also available in print format.
Keywords: Biodiversity -- Africa; Electronic books